A comparative analysis on harmony and arrangement of Sweet Dreams (Are Made of This) case study: Sweet Dreams (Are Made Of This) By Marilyn Manson / Muhammad Al-Hafiz Dolmat - Dolmat, Muhammad Al-Hafiz (2012)
The purpose of this thesis is to make a comparative on harmony and music arrangement of Eurythmics' Sweet Dreams (Are Made This). This study also compares Eurythmics' Sweet Dreams (Are Made This) harmonic structure and the music arrangement with the more recent version covered by the band, Marilyn Manson. Qualitative method was applied in this research; interview with a local composer, Prof Khairil Johari Johar, were chosen based on his involvement in composing and arranging music and even his prolonged experience in the local music industry. Samples were also cautiously chosen based on authoritative criteria. The principal conclusion was that both selected songs, that of from Marilyn Manson's cover and the original Eurythmics' have a very different in the sense of the genre of the song, instrumentation, mood and feel created from both songs. Also, the arrangement of these two songs varies from each other